Horizontal Variation in Surface Radiative Fluxes at SHEBA Camp. Version 1.0 ... - Curry, J. (UCAR/NCAR - Earth Observing Laboratory, 2007)
This dataset contains imagery of the horizontal variation in surface radiative fluxes from the SHEBA camp as a part of the Surface Heat Budget of the Arctic Ocean (SHEBA) Project. Data collected during 16 missions of the NCAR C-130 over the SHEBA camp during May and July are used to document the radiative environment at the surface. Specifically discussed are the characteristics of surface albedo under cloud conditions vaying from clear to solid overcast during spring and summer. The ice surface changed considerably during this time from snow-covered multiyear ice and mostly refrozen leads in May to bare multiyear ice, meltponds and open water in July. ...